Illustrating Semiotic Constructs: Exploring the Icon, Index, and Symbol in Advertisements for 'Some By Mi' Skincare Products - Ghenani, Ghenani; Sakinah, R. Myrna Nur (JETLEE : Journal of English Language Teaching, Linguistics, and Literature, 2024)
Abstract This study aimed to examine the role of semiotics in advertising, with a primary focus on the signifier and the signified. Acknowledging that advertising is a powerful tool to attract consumers’ interest, this study contended that precision in language usage is essential for efficiently convey the interest-bearing ads. This research employed a qualitative paradigm, wherein the data is systematically gathered, analysed, and expounded in accordance with the reserachers’ interpretation of the theoretical frameworks. To clarify this viewpoint, this study, thus, utilised Pierce’s semiotic theory of advertising, as the principal-analytical tool to scrutinise the meaning encoded in icon, index and symbols affixed to the products. Furthermore, the study emphasises the significant of Williamson's theoretical foundations as a framework in dealing with the complexity inherent in the investigation of semiotics in advertising, which defines advertising as both a borrowing principle and a social code, highlights the multiple dimensions of semiotics in the advertising domain. The findings attempt to shed light on the intricate dynamics of advertising through the lens of semiotics, providing a nuanced understanding of how symbols on skincare products contribute to the construction of meaning in advertising when viewed through a semiotic perspective.